Local People’s Perceptions of the Sumava National Park in the Czech Republic over a Span of Ten Years (1998-2008) - Gorner, Tomas; Najmanova, Klara; Cihar, Martin (Current Approaches in Science and Technology Research Vol. 2, 2021)
The Sumava National Park (NP), the largest protected area of its kind in Central Europe, is as interesting as it is problematic (historical development, conflicts between regional development and landscape protection). In order to evaluate the success of the Park’s policies, local park inhabitants’ attitudes were assessed over a ten-year period. Two surveys (N = 181 and N = 200) were conducted in August, 1998 and 2008. The questionnaires consisted of 43 queries from three thematic areas; (a) socio-demographic data, (b) environment and nature conservation, and (c) sustainable tourism and local development. The comparison of the results 1998 with 2008 showed that the Park inhabitants perceived living in the Park as improving and the scheme for nature conservation as either “optimal” or “more strict”. The surveys also showed the loss of job opportunities as the most prevalent local concern. In a cluster analysis based on perceptions of (a) the Park, (b) the environment and (c) Park Administration, subjects were divided into four opinion groups ranging from “optimists” to “grumblers”. The most “positive (optimistic)” group saw little connection between the Park’s existence and job losses, while the most “negative” group saw a strong connection in that regard. The Park management succeeded not only in handling the situation, but also in using it favorably throughout to improve the social climate amongst locals and also their acceptance of the NP.